Environmental Effects Evaluation of Innovative Renewable Energy Projects - SALNIKOVA, Anastasia A.; SLAVJANOV, Andrej S.; KHRUSTALEV, Evgenii Yu.; KHRUSTALEV, Oleg E. (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019DO - 10.14505//jemt.v10.1(33).10, 2019)
Developing sustainable renewable energy projects involves complex decision-making processes. At present time planning and developing of renewable energy projects across the globe imply calculation and consideration of negative environmental effects at all stages of energy project life cycle. The aim of the paper is to develop an environmental effects evaluation methodology based on ecological impact categories through all the stages of lifecycle of renewable energy technologies. We used data envelopment analysis to calculate the efficiency score for each renewable energy technology. EcoInvent database has been chosen as a source of eco-indicators. We suppose the efficiency ratio will remain unchanged when transferring estimates of the life cycle of renewable energy facilities to another territory. This allows us to use data obtained in other regions of the world to extrapolate comparative assessments and make the deliberate choice of the most environmentally preferable technology. The input-oriented DEA modelling has demonstrated geothermal and biogas technologies are the most preferable from an environmental point of view with the highest possible score. The least effective technologies are both modifications of PV with the minimum efficiency score. The results of the presented work indicated that DEA showed great promise to be an effective evaluating tool for future analysis on energy policy issues.